Integrating social governance principles: The role of diversity management and trust in fostering employee engagement - Darmawan, Aditya Angga; Sakapurnama, Eko (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: Diversity in Human Resource management is a challenge in a company. The development of technology, globalization, and migration encourage the acceleration of workforce diversity, especially in urban communities. The company's competitive advantage is the target of every company in carrying out its operations, one of the important factors driving this advantage is the management of Human Resources which leads to employee engagement. Diversity management is one of the aspects needed to increase employee engagement in employees. Methods: This study aims to analyze the effect of diversity management on employee engagement with organizational trust as a mediating variable. This study uses a quantitative research approach with purposive sampling data collection techniques conducted through a survey of 105 employees at PT BNI (Persero) Tbk. The data collected was then processed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method using SmartPLS 4 tools. Findings: The results of the study indicate that diversity management has a positive effect on employee engagement, both directly and through the role of organizational trust as mediation. In addition, organizational trust also has a positive effect on employee engagement. Novelty/Originality of this article: This article uniquely examines the mediating role of organizational trust in the relationship between diversity management and employee engagement using a quantitative SEM-PLS approach, offering empirical insight into ESG-aligned human resource strategies.